Conservation of the kinaselike regulatory domain is essential for activation of the natriuretic peptide receptor guanylyl cyclases. - Koller, K J (1992)
The natriuretic peptide receptors, NPR-A and NPR-B, are two members of the newly described class of receptor guanylyl cyclases. The kinaselike domain of these proteins is an important regulator of the guanylyl cyclase activity. To begin to understand the molecular nature of this type of regulation, we made complete and partial deletions of the kinase domain in NPR-A and NPR-B. We also made chimeric proteins in which the kinase domains of NPR-A and NPR-B were exchanged or replaced with kinase domains from structurally similar proteins. Complete deletion of the kinase homology domain in NPR-A and NPR-B resulted in constitutive activation of the guanylyl cyclase. Various partial deletions of this region produced proteins that had no ability to activate the enzyme with or without hormone stimulation. The kinase homology domain can be exchanged between the two subtypes with no effect on regulation. However, structurally similar kinaselike domains, such as from the epidermal growth factor receptor or from the heat-stable enterotoxin receptor, another member of the receptor guanylyl cyclase family, were not able to regulate the guanylyl cyclase activity correctly. These findings suggest that the kinaselike domain of NPR-A and NPR-B requires strict sequence conservation to maintain proper regulation of their guanylyl cyclase activity.